Accuracy degradation rate of LEO satellite-predicted orbits using different POD methods - Liu, J.; Wang, K.; Chen, B.; El-Mowafy, Ahmed; Allahvirdi-Zadeh, Amir; Yang, X. (2025)
To achieve high-accuracy positioning and timing in real time using Low Earth Orbit (LEO) navigation signals, the precision of the orbital products is of high necessity. Reduced-dynamic LEO satellite Precise Orbit determination (POD) can nowadays provide near-real-time orbits with an accuracy of centimeters, and real-time users can rely on broadcast LEO satellite ephemeris based on short-term prediction. However, in the case of experiencing observation data problems or satellite manoeuvers that are not performed as planned, large orbital errors or residuals could hamper the orbits from passing the self-check, and accordingly reduce their availability to users. In such a case, the kinematic POD delivers a redundant option. This study assesses the degradation rate of accuracy and integrity of the predicted orbits by applying different POD methods. It supports the selection of the best orbital type for real-time ephemeris fitting based on their near-real-time POD accuracy and the degradation rate of the prediction accuracy with the prediction time, assuming that different types of orbits might be generated at various times and thus require different prediction times for real-time applications. In this contribution, using 6 days of GPS and GPS/Galileo-combined dual-frequency phase and code observations tracked onboard Sentinel-3B (orbital altitude of about 810 km) and Satellite-6A satellites (about 1340 km), three types of predicted orbits are assessed. The degradation rates of the Orbital User Range Errors (OUREs) are calculated for predicted reduced-dynamic (RP), batch least-squares kinematic (KP), and filter-based kinematic (TP) orbits under different scenarios. The prediction rates for the three approaches amount to 4.2, 8.2, and 3.1 cm/h, respectively, for Sentinel-3B, and 2.6, 5.0 and 4.0 cm/h, for Sentinel-6A under the best-case scenario. Moreover, the integrity is analyzed using the 68.3%, 95.5% and 99.9% percentile lines. Within the 1 h of prediction time, the RP option exhibits the smallest OUREs, with maximum values of 6.7 cm (68.3% CL), 13.4 cm (95.5% CL), and 18.9 cm (99.9% CL), respectively, for Sentinel-3B, and 4.7, 10.1 and 15.6 cm, respectively, for Sentinel-6A. Overall, the RP method demonstrates the best precision and integrity under the same prediction period and normal near-real-time POD accuracy